Is wing morphology across birds associated with life history and sociality? - Beauchamp, Guy (Frontiers in Bird Science, 2023)
Wings in birds vary tremendously in size and shape across species. Ecological needs are thought to shape variation across species in wing morphology over evolutionary times. For instance, demands for energetic efficiency in species that fly long distances have produced long and narrow wings with a high aspect ratio. Demand for maneuverability in cluttered habitats or to escape predators more easily have favored wings with large areas relative to body size producing a low wing loading. The association between ecological needs and wing morphology is complex, however, and could involve other ecological variables. Here, I draw attention to two ecological factors that have received little attention, namely, life history and sociality. Species at the slow end of the life history continuum emphasize adult survival over reproduction and are considered risk averse. I predicted that such species would benefit from low wing loading and low aspect ratio to increase maneuverability and the ability to escape predators. More solitary species cannot rely on others in their groups to decrease predation risk. I predicted that such species should also benefit from low wing loading and low aspect ratio. Using data from the literature on wing loading and aspect ratio in a large number of species, I examined these predictions in a phylogenetic framework including several potentially confounding ecological variables that have been previously linked to wing morphology such as habitat, lifestyle, and migration. As predicted, more solitary species tended to have low wing loading and low aspect ratio. Low wing loading was also more common in species at the slow end of the life history continuum, but aspect ratio was higher than predicted. Overall, the results support the idea that life history and sociality can predict variation across species in wing morphology and highlight the effect of predation risk on the evolution of wing morphology in birds.